Identity and placemaking: understanding feelings of gentrification and discouraging displacement along Prospect Avenue in Kansas City, Missouri - Tokos, Regan L. (Kansas State University, 2019)
As Kansas City, Missouri continues to grow and reinvest in the downtown many residents on the periphery of the Central Business District are feeling threatened by displacement and “gentrification.” This report begins to address how the design of the urban landscape can be used to increase a sense of place and identity and to lessen the effects and threats of displacement. By using art, greenspace, and other additions to the physical environment, we can allow residents to express their identity and claim their community spaces as new people start to move in. Through this report I argue that expressing the history, culture, and identity of the chosen site will allow residents to feel more at home and more in control of their future even as it changes, develops, and even gentrifies. Change and growth are inevitable but taking current residents into account is vital to maintaining a successful community, especially on Kansas City’s East Side where residents have historically been an afterthought or deliberately disenfranchised. Building on the ideas of local residents, and exploring how design can meaningfully respond to resident needs and concerns, this report seeks to demonstrate a variety of functional and artistic ways to support the local community and maintain the unique identity of the northern section of Prospect Avenue Corridor.
Keywords: Placemaking; Kansas City; displacement